YTHDF2 destabilizes m6A-containing RNA through direct recruitment of the CCR4–NOT deadenylase complex - Hao Du (Nature Portfolio, 2016)
The YTHDF family of proteins are able to bind and regulate the stability of methylated N6 RNA. Here the authors show that this decreased m6A RNA stability is mediated by direct recruitment of the CCR4–NOT deadenylase complex through YTHDF proteins.